2023
DOI: 10.3390/pharmaceutics15030870
|View full text |Cite
|
Sign up to set email alerts
|

Digital Technologies Applied to Control the One-Step Process of Cannabis Olive Oil Preparations

Abstract: The reproducibility of an extemporaneous preparation is an essential condition for guaranteeing the quality, efficacy, and safety of the medicinal product. This study aimed to develop a controlled one-step process for cannabis olive oil preparations by applying digital technologies. For this purpose, the chemical profile of cannabinoid contents in oil extracts of Bedrocan, FM2, and Pedanios varieties obtained with the already in use method, proposed by the Italian Society of Compounding Pharmacists (SIFAP), wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…[1][2][3][4] There are several studies on the HPLC-based analysis of cannabis oil or CBD (5)-rich oil available in the literature for the period covered in this article. 44,97,[102][103][104][105][106][107][108][109][110][111][112] However, the analysis of cannabis oil using UHPL or UPLC has been limited to a few studies reported in the literature (Table 2).…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Cannabis Consumer Productsmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4] There are several studies on the HPLC-based analysis of cannabis oil or CBD (5)-rich oil available in the literature for the period covered in this article. 44,97,[102][103][104][105][106][107][108][109][110][111][112] However, the analysis of cannabis oil using UHPL or UPLC has been limited to a few studies reported in the literature (Table 2).…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Cannabis Consumer Productsmentioning
confidence: 99%
“…A simple UV-based detection was successful in identifying CBD (5), CBDA (6), Δ 9 -THC ( 14), and Δ 9 -THCA (15) in pharmaceutical grade cannabis oil, where Poroshell 120 EC-C 18 column (50 Â 3 mm, 2.7 μm) column was used with gradient elution comprising 0.1% HCOOH in water and 0.05% HCOOH in MeOH and a run time of only 11 min. 102 While the use of particle sizes much smaller than the usual particle size of 5 μm in analytical HPLC has increased in recent years, the use of columns of various lengths with 5 μm particle size appears to be quite common in cannabis oil analysis [103][104][105][106]108 (Table 2). In cannabis oil analysis, the most commonly used detector has been a UV detector including a PDA, but the use of MS detector 104 has also been observed.…”
Section: Hplc and Uplc (Or Uhplc) Analysis Of Cannabis Consumer Productsmentioning
confidence: 99%
See 3 more Smart Citations